Development Strategy of Traditional Culinary as a Sustainable Culinary Ecotourism Attraction in Semanu District, Gunungkidul - Resmayasari, Ira; Patabang, Melewanto; Kristianti, Hana; Dewi, Helianthi (LPPM Universitas Nusa Mandiri, 2025)
Traditional culinary heritage plays a crucial role as a cultural identity and a sustainable tourism attraction. This study aims to analyze the development strategy of traditional cuisine in Semanu District, Gunungkidul, using a descriptive qualitative approach with SWOT Analysis. The findings reveal key strengths in unique taste and traditional processing techniques (score 2.23), while weaknesses include conventional marketing and unstable raw material prices (score 1.01). Externally, opportunities arise from consumer preference and local resource potential (score 2.04), whereas threats stem from modern food competition and seasonal raw materials (score 1.00). The overall position of Semanu’s traditional cuisine falls in quadrant I (internal score +1.22; external score +1.04), so an intensive growth strategy is recommended. This strategy should include recipe preservation, product diversification, culture-based innovation, digital marketing, quality improvement, and capacity building for local entrepreneurs. Thus, Semanu’s traditional cuisine holds great potential as a sustainable culinary tourism attraction that supports cultural preservation and improves community welfare.